Design and performance evaluation through synchro-phasor signals for transient fault analysis in transmission lines and distributions - Nithyavelam, M.; Henry, Joseph (International Journal of Engineering and Technology, 2017)
Contemporary power supplies be obliged to offer trustworthy, superior-quality power. Hence, it is significant to facilitate the transmission line fault identification more precise, consistent and to be rectified immediately. In this paper, a unique organized interrelated structure for identifying the transient fault that occurs in transmission lines and distribution is proposed, by employing the Fast Fourier Transform (FFT). This technique utilizes synchrophasor measurements during disturbances found in transmission lines positioned in the network and compared the obtained flux phase with the reference signal that is 230V, 50Hz flux phase which is considered as the ideal condition. The obtained difference phase angle will provide the details of transients present in the given transmission lines present between the generator and the load. By employing this method, the Initial state of transient fault detection from phasor measurement as well as a Linear Regression Modelling for Transient Fault Detection also be able to be identified. This paper analysis the transient fault using synchro-phasors by comparing the existing fault detection with real-time implemented system.